Using a multifaceted quality improvement initiative to reverse the rising trend of cesarean births. (4th March 2018) - Ogunyemi, Dotun; McGlynn, Sara; Ronk, Anne; Knudsen, Patricia; Andrews-Johnson, Tonyie; Raczkiewicz, Angeline; Jovanovski, Andrew; Kaur, Sangeeta; Dykowski, Mark; Redman, Mark; Bahado-Singh, Ray
Abstract: Purpose: National efforts exist to safely reduce the rate of cesarean delivery, a major source of increased morbidity and healthcare costs. This is a report of a quality improvement study targeting reduction of primary cesarean deliveries. Materials and methods: From March 2014 to March 2016, interventions included a nested case-control review of local risk factors, provider and patient education, multidisciplinary reviews based on published guidelines with feedback, provider report cards, commitment to labor duration guidelines, and a focus on natural labor. Primary outcomes were the total primary singleton vertex and the nulliparous term singleton vertex (NTSV) cesarean delivery rates. Secondary outcome measures were postpartum hemorrhage, chorioamnionitis, perineal laceration, operative delivery, neonatal intensive care unit (NICU) admission, stillbirth, and neonatal mortality. Statistical process control charts identified significant temporal trends. Results: Control chart analysis demonstrated that the institutional cesarean delivery rate was due to culture and not "outlier" obstetricians. The primary singleton vertex cesarean rate decreased from 23.4% to 14.1% and the NTSV rate decreased from 34.5% to 19.2% (both p < .0001). There was a decrease in NICU admission but no significant changes in postpartum hemorrhage, chorioamnionitis, stillbirth, or neonatal mortality. Conclusions: Structured quality improvement initiatives may decrease primary cesarean deliveries without increasing maternal or perinatal morbidity.